Activation of alpha-globin transcription in primary mouse erythroid progenitors - Beagrie Robert; Oudelaar A. Marieke (University of Dundee, 2020)
Mammalian gene expression patterns are controlled by regulatory elements, which interact within Topologically Associating Domains (TADs). The relationship between activation of regulatory elements, formation of structural chromatin interactions and gene expression during development is unclear. Here, we present Tiled-C, a low-input Chromosome Conformation Capture (3C) technique. We use this approach to study chromatin architecture at high spatial and temporal resolution through in vivo mouse erythroid differentiation. In this dataset, we measure nascent transcription of the mouse alpha-globin genes by FISH using oligonucleotide probes that are specific for the alpha-globin introns. We measure the initial stages of alpha-globin upregulation in three subsets of early erythroid progenitors (S0-low, S0-medium and S1) and compare these to the levels observed in a positive control (mature, Ter119+ mouse erythroblasts) and in two negative controls (mouse primary brain, which does not express alpha-globin, and a no primary antibody control).
We performed RNA-FISH assays to determine the proportion of cells at three different stages of early erythroid differentiation that display nascent transcription of alpha-globin genes.
Keywords: Gene Regulation; Haemoglobin; RNA; Genetic transcription